GE_GERICHTE P/24739/2014 vom 12. Oktober 2017 - GE Cour de justice (2017)
ORDONNANCE PÉNALE ; OPPOSITION(PROCÉDURE) ; DÉFAUT(CONTUMACE) ; EXCUSABILITÉ ; NOTIFICATION ÉCRITE ; CITATION À COMPARAÎTRE | CPP.355.al2; CPP.85.al2; CPP.201